Studi Literatur Penerapan Metodologi Penilaian Barang Milik Negara Berupa Aset Tak Berwujud - Hutami, Rizka; Muhammad Fadli, Alif (Politeknik Keuangan Negara STAN, 2024)
Indonesia possesses substantial amount of national assets, both tangible and intangible. According to the aduited Laporan BMN 2022, the value of intangible assets (before the accumulation of amortization) as of December 31, 2022, was IDR 61.347 trillion. Furthermore, these intangible assets have the potential to serve as a significant source of national income from non-tax revenue. Government valuers can play a role in managing these state-owned intangible assets, including valuation and analysis for commercialization purposes. However, a study on the valuation methodologies for various types of intangibles is necessary. This study employs a literature review method, drawing from books, scholarly articles, research reports, and journals. The conclusion of this study is that government valuers need to consider criteria for selecting valuation approaches based on the requirements of the approaches themselves and the characteristics of the intangibles being valued. Valuation approaches are chosen based on whether the intangibles have transaction data available in the market, the ability to generate future cash flows, or whether both of these factors cannot be identified. Government valuers must also pay attention to the characteristics of software, patents and copyrights, licenses and franchises, research/valuation outcomes, and other intangible assets.